FAKTOR FAKTOR YANG MEMENGARUHI NIAT BELI KOSNUMEN TERHADAP KOSMETIK HALAL RAMAH LINGKUNGAN - Daffa, Aaliyah; Faisal, Aekram (JURSIMA, 2023)
This study aims to examine the influence of halal label, eco label, environmental knowledge, religiosity, and halal green awareness on purchase intention toward halal and environmentally friendly cosmetic products among female consumers in Indonesia. The research is grounded in the Theory of Planned Behaviour (TPB), which suggests that behavioral intention is influenced by attitude toward the behavior, subjective norms, and perceived behavioral control. A quantitative approach was employed using a survey method, targeting users of five halal and green cosmetic brands: Somethinc, Scarlett, MS Glow, Avoskin, and Wardah. The research design involved hypothesis testing, with data collected through a cross-sectional survey using online questionnaires completed by 200 respondents. Data analysis included validity and reliability tests, as well as Structural Equation Modeling (SEM) using JASP software. The results show that halal label, religiosity, and halal green awareness significantly affect purchase intention, while eco label and environmental knowledge have no significant effect. These findings are expected to serve as a reference for cosmetic industry stakeholders in developing marketing strategies that align with values of halal compliance and sustainability.